Associations between self-reported in-home smoking behaviours and surface nicotine concentrations in multiunit subsidised housing. Issue 1 (23rd October 2012) - Hood, Nancy E; Ferketich, Amy K; Klein, Elizabeth G; Pirie, Phyllis; Wewers, Mary Ellen
Abstract : Introduction: Smoke-free policies are being increasingly promoted and adopted in subsidised multiunit housing to address disparities in residential secondhand smoke exposure. In order to inform the planning and evaluation of these policies, this study examined associations between self-reported in-home smoking and surface nicotine concentrations. Methods: A face-to-face, cross-sectional survey was conducted from August to October 2011 with leaseholders in a probability sample of private subsidised housing units in Columbus, Ohio, without an existing smoke-free housing policy (n=301, 64% response rate). After the survey, a wipe sample was collected from a wood surface in the living room to measure surface nicotine concentrations (n=279). Results: In-home smoking was reported by 56.6% of respondents. Geometric mean surface nicotine concentrations differed between non-smoking and smoking homes (11.4 vs 90.9 μg/m 2 ; p<0.001), and between homes with complete, partial and no voluntary home smoking restrictions (8.9 vs 56.3 vs 145.6 μg/m 2 ; p<0.001). Surface nicotine concentrations were moderately correlated (r=.52) with the total number of cigarettes smoked indoors per week. Smoking behaviours of respondents, other household members and visitors, and length of stay were independently associated with surface nicotine concentrations in a multivariable model, explaining 52% of the variance. Conclusions: Surface nicotine concentrations were significantly associated with a range of self-reported in-home smoking behaviours. This measure should be considered for evaluating changes in in-home smoking behaviours after implementation of smoke-free policies by subsidised housing providers. More research is needed about how surface nicotine concentrations differ over space, time and various indoor surfaces.